Optimised controlled charging of electric vehicles under peak power‐based electricity pricing. Issue 6 (11th November 2020) - Simolin, Toni; Rauma, Kalle; Järventausta, Pertti; Rautiainen, Antti
Abstract : This study presents a practical control method for electric vehicle (EV) charging optimisation for detached and attached houses. The developed EV charging control method utilises real‐time measurements to minimise charging costs of up to two EVs in a single household. Since some Finnish distribution system operators have already launched peak power‐based distribution tariffs for small‐scale customers and because there is a lot of discussion on this kind of tariff development, the control method considers peak power‐based charges. Additionally, the proposed smart charging control method utilises charging current measurements as feedback to reallocate unused charging capacity if an EV does not utilise the whole capacity allocated for it. The control method is implemented and tested with commercial EVs. The conducted hardware‐in‐the‐loop simulations and measurements confirm that the control method works as intended. The proposed smart charging control reduces EV charging electricity distribution costs around 60% when compared to the uncontrolled EV charging.